Co-occurrence of genes for aerobic and anaerobic biodegradation of dichloroethane in organochlorine-contaminated groundwater. Issue 11 (12th October 2017) - Munro, Jacob E.; Kimyon, Önder; Rich, Deborah J.; Koenig, Joanna; Tang, Sihui; Low, Adrian; Lee, Matthew; Manefield, Mike; Coleman, Nicholas V.
Abstract: 1, 2-Dichloroethane (DCA) is a problematic groundwater pollutant. Factors influencing the distribution and activities of DCA-degrading bacteria are not well understood, which has hampered their application for bioremediation. Here, we used quantitative PCR to investigate the distribution of putative DCA-dehalogenating bacteria at a DCA-impacted site in Sydney (Australia). The dehalogenase genes dhlA, tceA and bvcA were detected in all groundwater samples (n = 15), while vcrA was found in 11/15 samples. The 16S rRNA gene sequences specific to the dehalogenating genera Dehalobacter, Desulfitobacterium and Dehalogenimonas were detected in 15/15, 13/15 and 13/15 samples, respectively, while Dehalococcoides sequences were found in 9/15 samples. The tceA, bvcA and vcrA genes occurred in the same samples as Dehalococcoides and Dehalobacter . Microcosm experiments confirmed the presence of bacteria capable of dechlorination under anoxic conditions. The abundance of the dhlA gene, which is found in hydrolytic DCA degraders, was positively correlated to the DCA concentration, and was unexpectedly most abundant in samples with low oxygen conditions. A dhlA -containing bacterium isolated from the site ( Xanthobacter EL8) was capable of anaerobic growth on DCA under denitrifying conditions. The presence of diverse DCA-dehalogenating bacteria at this site indicates that natural attenuation or biostimulation could be valid approaches for site cleanup. Abstract : Analysis of biodegradation genes at a contaminated site leads to the surprising finding that genes coding for both aerobic and anaerobic degradation processes are co-located in groundwater samples.